Enabling the development and deployment of next generation point-of-care diagnostics - Derda, R.; Gitaka, J.; Klapperich, C.M.; Mace, C.R.; Kumar, A.A.; Lieberman, M.; Linnes, J.C.; Jores, Joerg; Nasimolo, J.; Ndung'u, J.M.; Taracha, E.A.; Weaver, A.; et al. (Public Library of Science, 2015)
A major goal of the 1st International Point-of-Care Diagnostic Workshop in Nairobi, Kenya was to provide a forum for open dialog concerning current challenges in, and potential solutions for, the development of the next generation of POC diagnostics. The focus was not solely on descriptions of new technologies in development but also included demonstrations of their use in a field setting. The resulting conversations identified a number of obstacles to the successful translation of prototypes into field-deployable tools. These obstacles superseded those typically encountered in research; changes must be implemented at the institutional and governmental level to enable equitable collaborations between Western and African partners, and proper funding mechanisms must be established to support these collaborations. Additionally, this workshop showcased emerging technologies for POC tests and fostered new partnerships between technology developers and African research laboratories. Equitable partnerships are critical for the successful implementation of new POC technology. The attendees agreed that the most effective methods to effect change require improved communication of needs, ideas and abilities, and a conduit for the sharing of experiences and information. We plan to implement many of the changes that are suggested here in our own research programs and to use future conferences and workshops to guide the development of both technologies and partnerships. Our successes and failures will serve as models for those scientists striving to develop technological and biomedical solutions to similar problems in global health.